VARIASI MORFOMETRIK CANGKANG GASTROPODA FAMILY STROMBIDAE PADA EKOSISTEM LAMUN DESA SULI PULAU AMBON - Salmanu, Sriyanti I.A (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Morphometrics is a method of measuring the external forms of the body which is used as a basis for comparing fish sizes and can also be used to measure the shell morphology of gastropods. Morphometric measurements are useful for determining growth patterns, eating habits, groups and as a basis for identification. Method:. The method used in this research is a survey method on the seagrass ecosystem of Suli Village, Ambon Island. Shell morphometric measurements include shell length (SL), shell width (SW), spire height (SpH), apperture length (AL), shell opening width (AW), shell depth (SD), Results: The family of strombidae in the seagrass ecosystem of Suli Village, Ambon Island, found 3 species, namely Strombus lentiginosus, Strombus gibbosus. RodÃ¯ng, 1798, and Strombus labiatus RÃ¶ding, 1798, with varying morphometric sizes. Conclusion: The family of strombidae in the seagrass ecosystem of Suli Village, Ambon Island, found 3 species, namely Strombus lentiginosus, Strombus gibbosus and Strombus labiatus.